Hardware-in-the-loop Testing of Line Differential Protection Relay Based on IEC 61850 Process Bus - Palizban, Omid; Hafezi, Hossein; Kauhaniemi, Kimmo; Hämäläinen, Mikko (The Institution of Engineering and Technology, 2020)
The term digital substation refers to the process of managing operations between intelligent primary devices and distributed Intelligent Electric Devices (IEDs) interfaced with a highly secure communications network. The process bus is the first part of the interface between the primary instruments (such as the current and voltage transformers and protection devices) and is an important part of digitalization. This paper describes a method for constructing an interface between measurement instruments and protection devices based on the IEC 61850 standard. Two scenarios are considered to examine the performance of the power system protection in a transmission line between two substations. Both a conventional and an IEC 61850-9-2 (sampled values) approach are implemented to feed the measured values to the protection devices. Trip signals are then also sent to the circuit breakers using IEC 61850-8-1 (GOOSE message). Comparing this method with conventional technology, the outcomes for the digital substation are more accurate and reliable thanks to the rapid reaction of protection devices and the speed at which the trip signal is received. The new process bus method has been tested by implementing a hardware-in-the-loop platform, consisting of a real-time simulator (OPAL-RT eMEGAsim), StandAlone Merging Units (SAMUs), and line differential protection.
Keywords: Digital substation; IEC 61850 standard; Power system protection; Process bus; fi=Sähkötekniikka|en=Electrical Engineering|